Cadaveric study of accessory renal arteries and its surgical correlation - Saritha, S.; Jyothi, Naga; Kumar, M. Praveen; Supriya, G. (International Journal of Research in Medical Sciences, 2017)
A thorough knowledge of the accessory renal arteries has grown in importance with the increasing number of renal transplants and other uroradiological procedures. The literature indicates that multiple renal arteries are found in 9-75% cases. Normal anatomy describes each kidney receives irrigation from single renal artery which arises from abdominal aorta at the level L1-L2 vertebrae just below the superior mesenteric artery. Renal artery variations include their origin, number and course. The most common is the presence of additional vessels (accessory arteries) arising above the usual trunk is more frequent than one arising below. The accessory renal arteries are always end arteries. The kidneys may receive a single artery although each organ may equally be supplied by as many as six end arteries. The right and left renal arteries may arise from the aorta by a common stem or arise at lower point than usual in which case the kidneys lie below their usual position. There may be several renal arteries on each side or the renal artery may divide close to its origin into several branches. Current literature reports great variability in renal blood supply, the number of renal arteries mentioned being the most frequently found variation. Normal renal arterial information is useful not only for planning and performing of endovascular, laparoscopic uroradiological procedures and renal transplants. In order to facilitate the clinical approaches, we studied renal arterial pattern in 25 formalin fixed cadavers, on 50 kidneys during the period of one year. The purpose of this present study was to establish the incidence of accessory (aberrant) renal arteries in human cadavers and also discuss its surgical correlation during uroradiological procedures and angiographic interventions.